Knowledge, attitudes and behaviour regarding waste management options in Romania: results from a school questionnaire - KOLBE, Karin (Journal of Economic Development, Environment and People, 2014)
This study analyses knowledge, attitudes and behaviour in the area of different waste management approaches of pupils in Romania. Examining school students’ knowledge about waste management options and finding out the reasons that prevent them from participating in environmentally sound disposal options is essential for teachers and legislators. For this purpose, questionnaires were designed and distributed in two schools in Romania. The analysis revealed that knowledge is highly developed in Romania regarding the potential of recycling, while the concepts of waste management technologies are far less known about and understood. Landfill is seen as a problem for human health and the environment. However, recycling behaviour is low - partly as a result of limited possibilities. In general, the treatment hierarchy that is recommended in the "European waste hierarchy" is only partly reflected in students’ attitudes towards waste management options.